Practical Teaching Model with Lesson Study Based: An Effort in Increasing Future Arabic Language Teacher Professionalism - Abdurahman, Maman (EDUCARE, 2012)
ABSTRACT: Practical Teaching Program (PTP) is a program which must be taken by all university students in the education program. The purpose of PTP is, for the students (practitioners), to gain educational experience factually in the field, both with the school administration and its teaching-learning process. But in reality, there are numerous of students, who have finished their teaching exam in school who said that there are still confuse if they are going to be a professional teacher in the future. This research tries to explore the implementation of PTP based on Lesson Study (LS) principal and procedure. The method use is qualitative descriptive. This study conducted by Class Action Research: planning, action, observation, and reflection. The subjects of this research are 5 Arabic language students who are undergone PTP in the MAN (Madrasah Aliyah Negeri or State Senior High School for Islamic Education) 1 in Bandung, West Java, Indonesia. The instrument used to measures the professionalism of future Arabic language teacher are test, interview, observation, and direct supervision during the lesson study activity. The result shows that the PTP model of guidance and evaluation process with LS based can increase the professionalism of future Arabic language teacher which related to the pedagogic, professional, social, and personality of the teacher competencies. KEY WORDS: Practical teaching, lesson study, main supervisor, vice supervisor, Arabic language teacher, and professional competencies.About the Author: Dr. H. Maman Abdurahman is a Senior Lecturer at the Department of Arabic Language Education, Faculty of Language and Art Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. He can be reached at: marahman_180661@yahoo.co.idHow to cite this article? Abdurahman, Maman. (2012). âPractical Teaching Model with Lesson Study Based: An Effort in Increasing Future Arabic Language Teacher Professionalismâ in EDUCARE: International Journal for Educational Studies, Vol.4(2) February, pp.215-228. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 22, 2011); Revised (January 27, 2012); and Published (February 17, 2012).